2016
DOI: 10.1159/000444513
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Enrolment in Methadone Maintenance Therapy on Initiation of Heavy Drinking among People Who Use Heroin

Abstract: Background: There is equivocal evidence regarding whether people who use heroin substitute heroin for alcohol upon entry to methadone maintenance therapy (MMT). We aimed to examine the impact of MMT enrolment on the onset of heavy drinking among people who use heroin. Methods: We derived data from prospective, community-based cohorts of people who inject drugs in Vancouver, Canada, between December 1, 2005, and May 31, 2014. Multivariable extended Cox regression analysis examined the effect of MMT enrolment on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…Further, other work has suggested that MMT may also decrease the initiation of heavy drinking, further underlining the beneficial effects of opioid maintenance treatment on the health of people with opioid use disorders. 5 These findings could help inform future investigations into the role of heavy alcohol use, as described by the prospective study from India, 1 in the context of maintenance therapy.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Further, other work has suggested that MMT may also decrease the initiation of heavy drinking, further underlining the beneficial effects of opioid maintenance treatment on the health of people with opioid use disorders. 5 These findings could help inform future investigations into the role of heavy alcohol use, as described by the prospective study from India, 1 in the context of maintenance therapy.…”
Section: Discussionmentioning
confidence: 90%
“…5 The primary outcomes of interest were all-cause mortality and overdose (OD) mortality. Extended Cox regression analysis examined the bivariate association between heavy alcohol use and the time to death.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Caputo et al [28] demonstrated short term methadone treatment to be associated with a reduction in alcohol levels while long term methadone maintenance therapy resulted in increased alcohol consumption. While an inverse relationship between heroin use and alcohol use has previously been described [29, 30], a recent study found methadone enrolment to have no effect on heavy drinking and may even appear to decrease the initiation of heavy drinking among heroin users [31]. Furthermore, a 12-month longitudinal study of individuals with both heroin addiction and alcohol dependence demonstrated both methadone and buprenorphine to be associated with a reduction in alcohol use, with buprenorphine being more efficacious [32].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study found that participation in a methadone program did not increase the prevalence of heavy drinking among participants, addressing an ongoing concern about unintended consequences of OST program participation [6]. …”
Section: General Practice Vs Specialty Clinic-based Treatmentmentioning
confidence: 99%